PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH TERHADAP KOMPETENSI GURU - Faridah Yanti (Kelola: Journal of Islamic Education Management, 2021)
The study aims to determine the effect of principal democratic leadership on teacher competence, namely pedagogical competence, personality competence, professional competence and social competence. This research is a quantitative study using an ex-post facto research design. This study uses a quantitative approach, namely research that emphasizes numerical data (numbers) which are processed by statistical methods. The research was conducted at UPT SMAN 10 Luwu Utara. Population of 27 teachers and determination of the number of samples using the Slovin formula and get the results of 10 samples. The data management begins with the validity test and the instrument reliability test is obtained using SPSS version 22 for windows. The next step is the normality test, linearity test and finally the hypothesis test by performing a simple regression test Y = α + bX to determine the functional relationship of variable X with variables Y1, Y2, Y3, and Y4. Hypothesis testing uses the help of SPSS version 22 for windows. The results showed that the principal's democratic leadership style (X) had a positive and significant effect on teacher pedagogical competence (Y1), the principal's democratic leadership style had a positive and significant effect on the teacher's personality competence (Y2), the principal's democratic leadership style had a positive and significant effect. teacher professional competence (Y3), the principal's democratic leadership style has a positive and significant effect on teacher social competence (Y4).